Reversible recurrent profound thrombocytopenia due to linezolid in a patient with multi-drug resistant tuberculosis: A case report. Issue 34 (August 2018) - Wang, Ming-Gui; Wang, Dan; He, Jian-Qing
Abstract: Rationale: Thrombocytopenia caused by linezolid (LZD) is common, with a reported prevalence as high as 11.8%. Platelets typically reach normal levels 7 days after LZD withdrawal. However, recurrent profound thrombocytopenia due to LZD usage and a persistent profound drop in platelet count after LZD withdrawal have not been reported. Patient concerns: We report a case of a 75-year-old woman, who presented with recurrent profound thrombocytopenia induced by LZD treatment for multidrug-resistant tuberculosis (MDR-TB). Diagnoses: Laboratory data and symptoms during and after LZD usage and reusage indicated severe thrombocytopenia. Interventions: LZD was discontinued due to recurrent thrombocytopenia and the platelet count continued to drop for 9 days and returned to normal gradually 16 days after LZD withdrawal and supportive care including platelet transfusion. Outcomes: There was no recurrence of thrombocytopenia during 10 months of follow-up during treatment for MDR-TB with a regimen without LZD. Lessons: Recurrent profound thrombocytopenia can happen after several doses of LZD rechallenging. Therefore, reuse of LZD should be avoided after recovery from severe thrombocytopenia due to LZD.